Male infertile couples: an actor-partner interdependence model of attachment styles and fertility pressure - Huiling Qu; Guyu Liu; Xi Zhang; Xinmei Han; Lei Yan; Li Ge; Yuying Fang (BMC Psychiatry)
Abstract Background Couples undergoing artificial insemination by donor semen(AID) represent a unique group of infertility patients, the relationship between fertility pressure and attachment styles remains unclear. To investigate the fertility pressure and attachment dimensions in artificial insemination by donor semen(AID) couples, and develop an Actor-Partner Interdependence Model (APIM) for patient care. Methods This study is a cross-sectional study. From June to September 2021, couples who were about to receive AID treatment in our hospital were assessed using the Fertility Problem Inventory, and the Experiences in Close Relationships(ECR). Dyadic analysis applying the APIM was used. Results A total of 448 valid questionnaires were recovered, the effective response rate was 94.9%. The average score of men’s fertility pressure was higher than that of women’s(P = 0.021). The score of male attachment anxiety was higher than that of females(P = 0.038). Attachment avoidance(β = 0.46) and attachment anxiety(β = 0.33) in wives significantly impacted their fertility pressure. Attachment avoidance(β = 0.17) and attachment anxiety(β = 0.52) in husbands significantly impacted their fertility pressure. The attachment avoidance of wives’ had a significant impact on the husbands’ fertility pressure(β = 0.11). Conclusion Overall, the study revealed that in the couples who use donor sperm to expect pregnancy, the male has higher fertility pressure. Insecure attachment can cause more severe fertility pressure, fertility pressure is also affected by one’s partner.